(untitled) (diségno, 2023)
The Present of Architectural Drawing is the theme proposed by Paolo Belardi and Massimiliano Campi for this issue of the journal diségno and welcomed by the Editorial Board for several reasons. The first of these reasons concerns the close relationship between ideation, drawing and design, terms linked by a bond that is both theoretical and concrete; the second relates to the personalities of the two editors, who have always been interested in the themes of drawing projected towards design, exploring its theories and techniques of representation. [read more]